Source identification and temporal evolution of trace elements in PM10 collected near to Ny-Ålesund (Norwegian Arctic). (15th April 2019) - Conca, E.; Abollino, O.; Giacomino, A.; Buoso, S.; Traversi, R.; Becagli, S.; Grotti, M.; Malandrino, M.
Abstract: This study investigated the elemental composition of PM10 collected in a polar environment (Ny-Ålesund, Norwegian Arctic), to identify its sources and to understand the effects of short- and long-range transport processes. Natural (crustal and marine) and anthropogenic Arctic PM sources were identified, and specific emission sources were recognised by means of Principal Component Analysis and Hierarchical Cluster Analysis: airborne pollution deriving from ship fuels, local vehicle (non-exhaust) and continental emissions (e.g. incinerators or industries) were the main sources of anthropogenic elements. The results obtained so far from samples collected during four successive spring-summer sampling campaigns (2010–2013) show a remarkable seasonal trend for most of the investigated elements. For both geogenic and anthropogenic elements, concentrations are generally higher in March and April, when the ground is almost entirely covered by snow and ice, suggesting that long-range transport processes might be taking place. On the other hand, the concentrations of anthropogenic metals related to ship emissions (i.e. Co, Ni and V) peak in late spring and summer, when the marine traffic in the fjord is generally higher. For most of the analytes, the four campaigns were not significantly different; therefore, in the studied period, the composition of PM10 in Ny-Ålesund did not vary remarkably. Finally, the behaviour of Rare Earth Elements was discussed in terms of parent material mineralogy. Graphical abstract: Image 1 Highlights: Natural (geogenic and marine) and anthropogenic PM10 sources were identified. Anthropic element concentrations show a seasonal trend with maxima in spring. Airborne pollution from ship emissions was occasionally registered in summer. Anthropogenic element concentrations did not change over the examined years.